La collection de vases grecs du marquis de Northampton (1790-1851). Entre archéologie et sciences de la nature - Marie-Amélie Bernard (Les Cahiers de l'École du Louvre)
The Marquess of Northampton lived in Italy during the 1820s: there, he began a collection of Greek vases that he later added to in England through purchases at public sales. He was also a member of several learned societies, and had a keen interest in geology and mineralogy. The article examines the history of his collection and the principles behind its constitution in order to determine its relationship with the natural sciences.